Synergy of osmotic adjustment and antioxidant activity in Catalpa bungei: alleviating persistent drought stress from SL to NSL - Yu, Xiaochi; Wang, Junhui; Ma, Wenjun; Yi, Fei; Zhang, Peng (Frontiers in Plant Science, 2025)
IntroductionCatalpa bungei C. A. Mey is a precious timber and garden tree species native to China. It is mainly distributed in the semi-arid regions of northern China, where drought stress severely affects its growth.MethodsIn this study, we investigated the physiological responses and gene expression profiles of C. bungei seedlings subjected to a 28-day drought stress treatment.Results and discussionBy reducing stomatal conductance (Cond) and increasing proline (Pro) and soluble sugar contents (SS), C. bungei alleviated mild drought stress (7-14 days). Under moderate drought stress (14-21 days), a synergistic interaction of jasmonic acid (JA) and abscisic acid (ABA) enhanced catalase (CAT) activity and proline (Pro) content, while downregulating guard cell osmotic potential, thereby further decreasing stomatal conductance (Cond). Upon reaching severe drought stress (21-28 days, SWC 22%, LWC 73%), the activity of antioxidant enzymes and the content of osmotic substances continued to increase, while the structure of photosynthetic organs was damaged, resulting in a shift from stomatal limitation (SL) to non-stomatal limitation (NSL). Therefore, C. bungei mitigates mild drought stress through osmotic regulation, and ABA and JA coordinate antioxidant defenses and osmotic regulation as drought persists. Once the shift from SL to NSL caused by severe drought stress, the aforementioned mechanism ceases to be effective in mitigating the deleterious effects of drought stress on C. bungei. These findings enhance our comprehension of the mechanisms underlying C. bungei's response to prolonged drought, providing valuable insights for the precise evaluation of drought intensity and facilitating efficient management of C. bungei plantations.